Histopathological Profile of Therapeutic Doses of Mango Mistletoe Methanolic Extract (MMME) in Cardiac of Hypertensive Rats (DOCA-Salt) - Hakimah, Annisatul Anis; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid (JSMARTech, 2021)
This study determined the effect of Mango mistletoe Methanolic Extract (MMME) on the cardiac's histopathological profile of hypertensive rats (DOCA-Salt) treated. The MMME was treated on fifty rats for 14 days, divided into five treatments: negative control, positive control, doses 50, 100, and 200 mg/kg BW with five replications. One-way ANOVA analysis was used, namely JAMOVI with version 1.1.9.0, and for cell calculation, diameter using the IMAGE J application. Results showed that there were no significant differences in the histopathological profile of the cardiac in hypertensive rats (DOCA-Salt) treated with MMME for 14 days on the diameter of the heart muscle cells between the control (+) and control groups (-), treatments 1, 2, and 3. This is evidenced by the analysis of p-value> 0.05, namely 0.187 millimeters. Therefore, we concluded that MMME does not affect the diameter of heart/cardiac organ muscle cells. However, there was a significant difference in the amount of necrosis in the cardiac of hypertensive rats between control (+) and control (-) groups, treatments 1, 2, and 3. Based on the results, MMME reduces the number of necrosis in the heart/cardiac organ.